Model Proses Adopsi Teknologi di AgroIndustri Lada dengan Fuzzy Inference System - Suci Wulandari; Eriyatno; Meika Syahbana Rusli; B.S. Kusmuljono (Jurnal Optimasi Sistem Industri, 2011)
Technology, as one component of agroindustry development system, has a strategic role. It can only be realized if new technology is difussed and adopted. Adoption of technology in the processing of white pepper is still very low. It is therefore necessary to study with the aim to develop a model of agroindustry technology adoption process, and to formulate strategic policy for its acceleration. Model of measuring and predicting user acceptance of new technology is adopted from Unified Theory of Acceptance and Use of Technology (UTAUT) model. Mapping and prediction model technology adoption rates are expressed as a form of usage behavior. The model consists of two parts sub models namely intention to use sub models and support facilities sub model. To deal with vagueness in analysis of technology adoption, fuzzy inference system is used on mapping and level prediction of technology adoption.